Political Ideology, Community Openness and the Commons - Arvanitidis, Paschalis; Nasioka, Foteini (Sens public)

(untitled) (Département des littératures de langue française, 2024)
Vacant urban spaces are underutilized resources under threat that can be used to improve the quality of urban life and urban dwellers’ well-being. Yet, traditional (state or market oriented) approaches have failed to bring them to life, due to lack of necessary funds, investment interest or/and deficiencies in property rights. It has been argued (by scholars of different perspectives) that managing these spaces as commons constitutes a successful and sustainable practice, capable to address the social, political, environmental and nutritional needs of the respective community. Yet, the issue of defining this community remains controversial among commons’ scholars. Should the boundaries around the community be strict or fuzzy, and how important is group specification for the success of commons endeavours? The current paper aims to shed light to these questions. In particular, it seeks to explore the role that political ideology plays in prescribing community boundaries and the effect this (usually unspoken) rule has in the sustainable management of the resources. In doing so the paper employs the social–ecological systems (SES) framework to analyse two urban community garden initiatives of urban commons located in Athens, Greece, that differentiate on the degree by which membership is open and subject to political conviction. We find that adherence to a specific political ideology may increase community coherence but jeopardizes the sustainable management of the common resource, since the latter simply becomes a means of political expression, rather than the primacy concern of the group. This finding has certain implications for both theory and policy.